Characterization and Antioxidant Activity of Mahogany Bark Extract-loaded Chitosan Nanoparticles - Syamsul Falah; Sulistiyani Sulistiyani; Dimas Andrianto (Masyarakat Peneliti Kayu Indonesia, 2012)
Nanoparticles-based drug delivery has been recognized to improve the solubility of poorly water-soluble drugs, prolong the half-life of drug systematic circulation by reducing immunogenicity, and releases drugs at a sustain rate. The present study reports on the characterization of mahogany bark extract-loaded chitosan nanoparticles and their antioxidant activity. Mahogany bark meal was extracted in boiled water for four hours. Chitosan-sodium tripolyphosphate (STPP) nanospheres were sonicated with ultrasonicator to obtain chitosan-STTP nanocapsules for 30 and 60 min and then were dried with spray dryer. The chitosan-STPP nanocapsules loaded by mahogany extract were then analysed for surface morphology and physical state by scanning electron microscope (SEM) and X ray diffraction (XRD), respectively. Antioxidant activity of the nanoparticles was evaluated by scavenging the 1,1-diphenyl-2-picrylhydrazyl (DPPH) using free radical method. Based on SEM data, the nanoparticle shapes were viewed to adhere to spherical shape. Spherical chitosan-STTP nanoparticles loaded with mahogany bark extract were obtained in the size range of 480 2000 nm and 240 1000 nm for 30 and 60 min of ultrasonication time, respectively. The antioxidant activity of the nanoparticles was lower than that of the native mahogany bark extract.